Layers of perception: proceedings of the 35th International Conference on Computer Applications and Quantitative Methods in Archaeology (CAA) ; Berlin, Germany, April 2-6, 2007 - Posluschny, Axel; Lambers, Karsten; Herzog, Irmela (Kolloquien zur Vor- und Frühgeschichte, 2008)
Literaturangaben